MENGGALI MAKNA MOTIF HIAS BEJANA PERUNGGU NUSANTARA: PENDEKATAN STRUKTURALISME LEVI-STRAUSS - Hafiful Hadi Sunliensyar (BRIN, 2017)
One of Dong Son Culture product is bronze vessels where found in some areas of Indonesia that is Kerinci, Madura, Lampung, Kalimantan dan Subang. Study about bronze vessels is limited on form and ornament description, and analysis. Ornamental study used structrulism approach on bronze vessels was not done. the purpose of this research is to know about bronze vessels structure and to give new meaning about it with Levi-Strauss structuralism approach. From the data and reference study was known that ornament on bronze vessels is an abstract of ideology/ way of life and ideas of their belonging community. These ideas formed a dualism, such